Cholesterol-to-lymphocyte ratio (CLR)-based nomogram as a prognostic tool in nasopharyngeal carcinoma: a large-scale long-term retrospective study - Jing Yuan; Wei-Qiong Ni; Yong-Miao Lin; Ao-Qiang Chen; Zhi-Qing Long; Si-Fen Wang; Fang-Fang Duan; Chao Zhang; Xin Huang; Xue-Wen Zhang; Xin-Yu Liu; Wen Xia; et al. (European Journal of Medical Research)
Abstract Background Nasopharyngeal carcinoma (NPC) is a prevalent malignancy characterized by variable outcomes, even after standardized treatment protocols. The American Joint Committee on Cancer (AJCC)/Union for International Cancer Control (UICC) staging system has proven limited in its ability to predict survival, which highlights the necessity for the discovery of new biomarkers. Methods This study was a retrospective analysis of 842 NPC patients who received platinum-based concurrent chemoradiotherapy (CCRT). The cholesterol-to-lymphocyte ratio (CLR) was calculated and evaluated as a potential prognostic factor. Both univariate and multivariate analyses were conducted to pinpoint independent prognostic variables. Furthermore, CLR-based nomograms were developed and assessed for its predictive accuracy. Results Low CLR (≤ 3.06) was significantly linked to both improved overall survival (OS; HR = 0.640, 95% CI 0.473–0.866, P < 0.001)and progression-free survival (PFS; HR = 0.754, 95% CI 0.586–0.970, P = 0.028). Multivariate analysis confirmed CLR as an independent prognostic factor for OS (but only in univariate analysis for PFS). Additionally, age, tumor stage, nodal stage, and body mass index were independently associated with both OS and PFS in multivariate analysis. The CLR-based nomogram showed superior discriminative performance compared to the traditional staging system, with higher C-indices for both OS(0.668 vs 0.635) and PFS (0.655 vs 0.625). Conclusions CLR stands as an independent prognostic factor for NPC patients undergoing CCRT. The CLR-based nomogram (incorporating five independent prognostic factors: age, T stage, N stage, BMI, and CLR) provides a tailored approach to predicting survival, enabling healthcare providers to adjust treatment strategies in accordance with individual risk profiles. Further validation of these findings in external cohorts is necessary, as well as exploration of CLR's clinical utility in directing treatment decisions.